Manajemen Wisata Di Kawasan Hutan Lindung Oleh Kelompok Tani Hutan Pink Lestari Desa Sekaroh Kecamatan Jerowaru - Abdurrahim; Nasrullah; Herman Satria (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2024)
Management is a helpful process that formulates wisdom and purpose and gives supervision of all things involved in the implementation and achievement of objectives. Study This aims: 1) to know management management tour pink beach by group farmer sustainable pink forest. 2) for knowing influence group farmer sustainable pink forest in tour pink beach in the forest area protect. The type of research used is a study approach, with data obtained with observation, interviews, and documentation. Validity of researcher data uses technique triangulation. The data collection techniques used are qualitative. Implementation This data collection also involves various activities supporting others, like creating rapport, selecting informants, and recording data/information results in data collection. Research results show that: 1) management management of the Sustainable Pink Forest Farmer Group at Pink Beach tourism-based service environment in forest areas protect. Management tourism in forest areas protector who has object tour, of course, must involve all stakeholders to use maximizing management. As well as collaboration from all parties Good government or society to basic benefit from an object tour the society can feel it directly. 2) The influence of the Pink Lestari Forest Farmer Group on the Pink Beach tour. The existence of the Pink Lestari Forest Farmer Group which is managed by the community local gets profit in development tours. If development, development as well as management tours continue to improve, of course, will interest more Lots travelers local and abroad For Keep going visit Pink Beach Alone. With so, there is no close possibility that the public will Keep going to get advantages. There are several influences of the Pink Lestari Forest Farmers Group on Pink Lestari Tourism including: a) Influence Social Community Culture and Economy. b) Influence Environment.